AFFECTS OF TSUNAMI ON SOIL PROPERTIES IN NAD AND ITS REHABILITATION STRATEGY - RACHMAN, ACHMAD; ERFANDI, DEDDY; ERFANDI, DEDDY; ALI, M. NASIL; ALI, M. NASIL (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2008)
The giant tsunami waves following the earthquake of the west coast of Sumatra on December 26, 2004, have caused soil salinisation of agricultural lands and damaged to irrigation and drainage channels along the coastal areas of Aceh Province, Indonesia. The objective of this study was to monitor the changes in soil salinity of the tsunami-affected sites. Regular collection of soil samples for soil laboratory analyses and field salinity measurement using an electromagnetic induction technique(EM38) have been conducted. The level of soil salinity in tsunami affected areas appears to be related to the characteristics of the deposited mud and soil permeability. Salt appears to have penetrated deeper into the sandier soils, commonly used to grow peanut during dry seasons. In the heavier rice soil, salt accumulate closer to the soil surface, probably because they were flooded at the time of the tsunami and often have a dense impermeable plough layer. Recommendations have been made to farmers that would allow them to reduce crop losses on tsunami affected soils. This includes avoid planting land that is still saline, enhance salt leaching horizontaly and vertically, improve soil fertility, and grow salt tolerant crops.